An Analysis of Students’ Writing Ability in Recount Texts - Sopian Saori; Sugianto Sugianto (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The research aimed to investigate the students’ ability and to explore the students’ difficulties in writing recount text. This research used a case study, the research design was presented using descriptive qualitative method. The subject of the study was the first year students of MA NW Nabi’ Nubu’ Kekait which consists of 25 students. Writing test and interview were the instrument of the research. The result of the study showed that the mean score of students was 69.92. It means that the students’ ability in writing recount text was poor. There were three students (12%) got below 60 and categorized as poor. Ten students (40%) got 61-70 categorized poor. Nine students (36%) got 71-80 categorized average, and three students (12%) categorized very good. Meanwhile, having analyzed the students’ ability in each of the writing aspects. Vocabulary and organization were categorized good to average whereas content, grammar, and mechanic were fair to poor category. Based on the result of the study, it can be concluded the students found it difficult in grammar, content, and mechanic. It is suggested for English teacher should give the students more practice in writing to improve their content and grammar in writing recount text.